Evaluation of some fungitoxicants for controlling tomato early blight disease - El-Fiki, I. A.I. (Journal of Phytopathology and Disease Management, 2017)
Three different fungitoxicants, i.e., Trichoderma harzianum, Bacillus subtilis and Roxil Plus WP50 fungicide, were investigated against tomato early blight disease caused by Alternaria solani fungus in vitro and in vivo. By using dual culture technique, the highest reduction percentage of A. solani growth was recorded with B. subtilis followed by Roxil treatments, while Roxil followed by T. harzianum treatments recorded highest reduction percentage of sporulation. Meanwhile, by using poisoned food technique the highest reduction percentage of A. solani growth was recorded with Roxil followed by B. subtilis treatments, while B. subtilis recorded highest reduction percentage of sporulation. Three fungitoxicants were investigated as foliar spray for their abilities for controlling early blight disease on naturally infected tomato plants under open field conditions. Roxil fungicide followed by B. subtilis treatments caused the highest significant reduction in disease incidence and disease severity percentage during the two successive growing seasons 2013/14 and 2014/15. Concerning to yield parameters, Roxil and T. harzianum treatments were significantly increased total yield weight and average weight of tomato fruit. Moreover, all tested treatments increased clearly total phenol content, peroxidase, polyphenoloxidase and chitinase activities, as well as, vitamince C contents as compared to control treatment.